(NrAS^ETNYE METODY W FIZI^ESKOJ HIMII (B:s (NmEVWUZOWSKIJ TEMATI^ESKIJ SBORNIK NAU^NYH TRUDOW (B/s - (NpAPULOW(B, (N`(B.(Ng(B.s; (NkALININSKIJ GOSUDARSTWENNYJ UNIWERSITETs ((NkALININ (B:s (NiZD(B-(NWO kALININSKOGO GOS(B. (NUN(B-(NTA(B,s, 1987)
(NbIBLIOGR(B. 165s
Keywords: (NtEORETI^ESKAQ HIMIQs